On the Offensive: The Role of Outer Membrane Vesicles in the Successful Dissemination of New Delhi Metallo-b-lactamase (NDM-1) - Martínez, Melina María Belén; Bonomo, Robert A.; Vila, Alejandro J.; Maffia, Paulo César; González, Lisandro J. (American Society for Microbiology, 2021)
The emergence and worldwide dissemination of carbapenemase-producing Gram-negative bacteria are a major public health threat. Metallo-b-lactamases (MBLs) represent the largest family of carbapenemases. Regrettably, these resistance determinants are spreading worldwide. Among them, the New Delhi metallo-b-lactamase (NDM-1) is experiencing the fastest and largest geographical spread. NDM-1 b-lactamase is anchored to the bacterial outer membrane, while most MBLs are soluble, periplasmic enzymes. This unique cellular localization favors the selective secretion of active NDM-1 into outer membrane vesicles (OMVs). Here, we advance the idea that NDM-containing vesicles serve as vehicles for the local dissemination of NDM-1. We show that OMVs with NDM-1 can protect a carbapenem-susceptible strain of Escherichia coli upon treatment with meropenem in a Galleria mellonella infection model. Survival curves of G. mellonella revealed that vesicle encapsulation enhances the action of NDM-1, prolonging and favoring bacterial protection against meropenem inside the larva hemolymph. We also demonstrate that E. coli cells expressing NDM-1 protect a susceptible Pseudomonas aeruginosa strain within the larvae in the presence of meropenem. By using E. coli variants engineered to secrete variable amounts of NDM-1, we demonstrate that the protective effect correlates with the amount of NDM-1 secreted into vesicles. We conclude that secretion of NDM-1 into OMVs contributes to the survival of otherwise susceptible nearby bacteria at infection sites. These results disclose that OMVs play a role in the establishment of bacterial communities, in addition to traditional horizontal gene transfer mechanisms. IMPORTANCE Resistance to carbapenems, last-resort antibiotics, is spreading worldwide, raising great concern. NDM-1 is one of the most potent and widely disseminated carbapenem-hydrolyzing enzymes spread among many bacteria and is secreted to the extracellular medium within outer membrane vesicles. We show that vesicles carrying NDM-1 can protect carbapenem-susceptible strains of E. coli and P. aeruginosa upon treatment with meropenem in a live infection model. These vesicles act as nanoparticles that encapsulate and transport NDM-1, prolonging and favoring its action against meropenem inside a living organism. Secretion of NDM-1 into vesicles contributes to the survival of otherwise susceptible nearby bacteria at infection sites. We propose that vesicles play a role in the establishment of bacterial communities and the dissemination of antibiotic resistance, in addition to traditional horizontal gene transfer mechanisms.
Keywords: Ciencias naturales::Ciencias biológicas::Biología celular, Microbiología